ALTERING THE FUNCTION OF PADDY FIELDS TOWARD IRRIGATION NETWORKS IN PIDIE DISTRICT: A Study of Pidie Qanun No. 3 of 2023 and Al-Milkiyyah Theory - Revi, Jihan Friska (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2025)
The conversion of paddy fields, especially in technically irrigated areas, is a critical issue in the Pidie District, Aceh Province. The Pidie District Government is addressing this challenge through the enactment of Qanun No. 3 of 2023, which aims to limit the conversion of paddy fields to preserve land for agricultural purposes. The purpose of this study is to assess the application of the Qanun from the perspective of Islamic law through the concept of al-milkiyyah. The research was conducted with a juridical-sociological approach, using a descriptive qualitative method. The data in this study were obtained from interviews with the Agriculture Office, as well as a documentation review of related regulations and Islamic law literature. The results show that although Qanun No. 3 of 2023 strictly prohibits the conversion of paddy fields in technical irrigation areas, its implementation still faces obstacles due to a lack of socialisation and law enforcement. The perspective of Islamic law emphasises the importance of land management, adhering to the principle of people's maslahat, which ensures that restrictions on land conversion align with Sharia values. This research concludes that restrictions on land use change not only preserve the sustainability of agricultural land but also fulfil the objectives of Sharia in maintaining community welfare.